Software-based self-testing methodology for processor cores. - Li Chen (IEEE Transactions on computer-aided design of integrated circuits and systems)
At-speed testing of gigahertz processors using external testers may not be technically and economically feasible. Hence, there is an emerging need for low-cost high-quality self-test methodologies that can be used by processors to test themselves at-speed. Currently, built-in self-test (BIST) is the primary self-test methodology available. While memory BIST is commonly used for testing embedded memory cores, complex logic designs such as microprocessors are rarely tested with logic BIST. In this paper, we first analyze the issues associated with current hardware-based logic-BIST methodologies by applying a commercial logic-BIST tool to two processor cores. We then propose a new software-based self-testing methodology for processors, which uses a software tester embedded in the processor memory as a vehicle for applying structural tests. The software tester consists of programs for test generation and test application. Prior to the test, structural tests are prepared for processor components in the form of self-test signatures. During the process of self-test, the test generation program expands the self-test signatures into test sets and the test application program applies the tests to the components under test at the speed of the processor. Application of the novel software-based self-test method demonstrates its significant cost/fault coverage benefits and its ability to apply at-speed test while alleviating the need for high-speed testers